N-Hydroxysuccinimide crosslinked graphene oxide–gold nanoflower modified SPE electrode for sensitive detection of chloramphenicol antibiotic. Issue 26 (27th April 2021) - Ali, M. R.; Bacchu, M. S.; Al-Mamun, M. R.; Ahommed, M. S.; Saad Aly, M. Aly; Khan, M. Z. H.
Abstract : Here we introduce a composite material that consists of graphene oxide (GO) sheets crosslinked with N -hydroxysuccinimide (NHS) and functionalized with gold nanoflowers (AuNFs). Abstract : Here we introduce a composite material that consists of graphene oxide (GO) sheets crosslinked with N -hydroxysuccinimide (NHS) and functionalized with gold nanoflowers (AuNFs). Furthermore, a screen printed electrode (SPE) modified with the introduced composite is electrochemically reduced to obtain an SPE/rGO–NHS–AuNFs electrode for sensitive and selective determination of chloramphenicol (CAP) antibiotic drug. The morphological structure of the as-prepared nanocomposite was characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, cyclic voltammetry, Fourier-transform infrared spectroscopy and electrochemical impedance spectroscopy. The proposed sensor demonstrated excellent performance with a linear concentration range of 0.05 to 100 μM and a detection limit of 1 nM. The proposed electrode offers a high level of selectivity, stability, reproducibility and a satisfactory recovery rate for electrochemical detection of CAP in real samples such as blood serum, poultry feed, milk, eggs, honey and powdered milk samples. This further demonstrates the practical feasibility of the proposed sensor in food analysis.